Solvability of a Quadratic Integral Equation of Fredholm Type with Supremum in Hölder Spaces - J. Caballero Mena; R. Nalepa; K. Sadarangani (Journal of Function Spaces)
Using the classical Schauder fixed point theorem, we prove the existence of solutions of a quadratic integral equation of Fredholm type with supremum in the space of functions satisfying the Hölder condition.